Rethinking of ureteral stent removal using an extraction string; what patients feel and what is patients' preference? : a randomized controlled study. Issue 1 (December 2015) - Kim, Dae; Son, Jeong; Jang, Seok; Lee, Jae; Cho, Dae; Lim, Chae
Abstract Background Ureteral stent removal using an extraction string is advantageous because it can obviate an invasive cystoscopy, but there is a paucity of data on how patients feel about it, and how bothersome or beneficial it is. We performed this study to evaluate patients' preference for stent removal using an extraction string and which parameters could affect it. Methods In total, 114 consecutive patients undergoing ureteral stent insertion after ureteroscopic stone removal (URS) for unilateral recurrent ureter stones were enrolled. Patients were randomized to a string group or a no string group. Stent removal was performed on the first visit within 7 days postoperatively. All patients were asked to complete the ureteral stent symptom questionnaire, to rate the degree of pain during stent removal using a visual analog scale (VAS) and to answer to questions regarding their preference. Results No significant differences were found in domain total scores including urinary symptoms (p = 0.17), pain (p = 0.62), general health (p = 0.37), work performance (p = 0.41). However, regarding separate questions for 'dysuria' and 'difficulties with heavy physical activity', there were significant intergroup differences (p = 0.03 and p = 0.04, respectively). Particular, a significantly higher proportion of patients in the string group checked 'stoppage of sexual intercourse due to stent-related problems' than in the no string group (p = 0.03). VAS score on stent removal was significantly higher in the no string group than the string group (p = 0.005). Among the patients who remember the experience of an indwelling ureteral stent in the past, 85 % (17/20) of the no string group answered 'No' to the question of 'difference between the methods used in this time and in the past'. On the contrary, 84.2 % (16/19) answered 'Yes' to the same question in the string group. And, all 16 patients of the string group who noted differences between the methods preferred ureteral stent removal using an extraction string to the past method. Conclusions Despite of minor increased morbidity related to the extraction string, patients preferred ureteral stent removal using the extraction string after URS. The patients with the extraction string felt less pain on stent removal than flexible cystoscopic stent removal. Trial registration KCT0001700 . The trial was registered in the Clinical Research Information Service (CRiS), Republic of Korea; registration date: 18/11/2015.